Antecedents of cross-functional integration level and their organizational impact. Issue 8 (7th October 2019) - Ferreira, Ana Cristina; Pimenta, Marcio Lopes; Wlazlak, Paraskeva
Abstract : Purpose: The purpose of this paper is to develop a model to predict the antecedents of the integration level among marketing, logistics and production, considering the influence of formal and informal factors that generate integration and the existence of conflicts. Design/methodology/approach: A survey of 179 participants from all regions of Brazil was conducted. A parsimonious model including four dimensions and 34 variables was developed through confirmatory factor analysis and structural equation modeling. Findings: The field data corroborate studies dealing with the impact of various formal and informal integration factors on the cross-functional integration level as a construct. Furthermore, this paper concludes that the level of cross-functional can be defined as: the intensity of the relationship among internal functions which can be measured by the mutual existence of formal and informal factors and the absence of manifest conflicts. Research limitations/implications: The findings of this paper cannot be generalized because of the convenience sampling. Future research could apply a probabilistic sampling and try to explore other geographical settings in both national and international contexts. Practical implications: The proposed model can generate important information for managers by pointing out variables that can predict the integration level and their impacts on the organizational performance. The paper concludes with examples about how the model could be useful in several practical situations. Originality/value: This paper proposes a model with reasonable accuracy to predict the integration level and overcomes prior research limitations with respect to models to predict the antecedents of the integration level, particularly the role of conflicts in the integration processes.